Genome-Wide Identification of R2R3-MYB Transcription Factors: Discovery of a “Dual-Function” Regulator of Gypenoside and Flavonol Biosynthesis in Gynostemma pentaphyllum - Huang, Ding; Ming, Ruhong; Xu, Shiqiang; Yao, Shaochang; Li, Liangbo; Huang, Rongshao; Tan, Yong (Frontiers in Plant Science, 2022)
The R2R3-MYB gene family participates in several plant physiological processes, especially the regulation of the biosynthesis of secondary metabolites. However, much less is known about the functions of R2R3-MYB genes in Gynostemma pentaphyllum, a traditional Chinese medicinal herb that is an excellent source of gypenosides (a class of triterpenoid saponins) and flavonoids. In this study, a systematic genome-wide analysis of the R2R3-MYB gene family was performed using the recently sequenced G. pentaphyllum genome. In total, 87 R2R3-GpMYB genes were identified and subsequently divided into 32 subgroups based on phylogenetic analysis, which supported by conserved exon–intron structures and motif compositions within same subgroup. Collinearity analysis demonstrated that segmental duplication events were majorly responsible for the expansion of the R2R3-GpMYB gene family, and Ka/Ks analysis indicated that the majority of the duplicated R2R3-GpMYB genes underwent purifying selection. A combination of transcriptome analysis and qRT-PCR confirmed that GpMYB81 along with genes encoding gypenoside and flavonol biosynthetic enzymes exhibited similar expression patterns in different tissues and response to methyl jasmonate (MeJA). Moreover, GpMYB81 could bind to the promoters of GpFPS1 and GpCHS, the key structural genes of gypenoside and flavonol biosynthesis, respectively, and activate their expression. Altogether, this study highlights a novel transcriptional regulatory mechanism that suggests that GpMYB81 acts as a ‘dual function’ regulator of gypenoside and flavonol biosynthesis in G. pentaphyllum.